Soybean oil-based HFD induces gut dysbiosis that leads to steatosis, hepatic inflammation and insulin resistance in mice - Jacob, Texy; Sindhu, Sardar; Hasan, Amal; Malik, Md. Zubbair; Arefanian, Hossein; Al-Rashed, Fatema; Nizam, Rasheeba; Kochumon, Shihab; Thomas, Reeby; Bahman, Fatemah; Shenouda, Steve; Wilson, Ajit; et al. (Frontiers in Microbiology, 2024)
High-fat diets (HFDs) shape the gut microbiome and promote obesity, inflammation, and liver steatosis. Fish and soybean are part of a healthy diet; however, the impact of these fats, in the absence of sucrose, on gut microbial dysbiosis and its association with liver steatosis remains unclear. Here, we investigated the effect of sucrose-free soybean oil-and fish oilbased high fat diets (HFDs) (SF-Soy-HFD and SF-Fish-HFD, respectively) on gut dysbiosis, obesity, steatosis, hepatic inflammation, and insulin resistance. C57BL/6 mice were fed these HFDs for 24 weeks. Both diets had comparable effects on liver and total body weights. But 16S-rRNA sequencing of the gut content revealed induction of gut dysbiosis at different taxonomic levels. The microbial communities were clearly separated, showing differential dysbiosis between the two HFDs. Compared with the SF-Fish-HFD control group, the SF-Soy-HFD group had an increased abundance of Bacteroidetes, Firmicutes, and Deferribacteres, but a lower abundance of Verrucomicrobia. The Clostridia/Bacteroidia (C/B) ratio was higher in the SF-Soy-HFD group (3.11) than in the SF-Fish-HFD group (2.5).Conversely, the Verrucomicrobiacae/S24_7 (also known as Muribaculaceae family) ratio was lower in the SF-Soy-HFD group (0.02) than that in the SF-Fish-HFD group (0.75). The SF-Soy-HFD group had a positive association with S24_7, Clostridiales, Allobaculum, Coriobacteriaceae, Adlercreutzia, Christensenellaceae, Lactococcus, and Oscillospira, but was related to a lower abundance of Akkermansia, which maintains gut barrier integrity. The gut microbiota in the SF-Soy-HFD group had predicted associations with host genes related to fatty liver and inflammatory pathways. Mice fed the SF-Soy-HFD developed liver steatosis and showed increased transcript levels of genes associated with de novo lipogenesis (Acaca, Fasn, Scd1, Elovl6) and cholesterol synthesis (Hmgcr) pathways compared to those in the SF-Fish-HFD-group. No differences were observed in the expression of fat uptake genes (Cd36 and Fabp1). The expression of the fat efflux gene (Mttp) was reduced in the SF-Soy-